Common mental disorders among Irish jockeys: prevalence and risk factors - King, L.; Cullen, S. J.; O`Connor, S.; McGoldrick, A.; Pugh, J.; Warrington, G.; Woods, G.; Nevill, A. M.; Losty, C. (The Physician and Sportsmedicine, 2021)
Objective Jockeys compete in a sport, horseracing, renowned for its physical and psychological demands. Previous research has identified that common mental disorders (CMDs) may be prevalent among this unique population of athletes. The aim of the present study was to further explore the prevalence of CMDs among jockeys and to test for associations with potential risk factors.